(untitled) (Indian Journal of Animal Production and Management, 2014)
The study was conducted in Kamrup district of Assam. Assam Agricultural Competitiveness Project (AACP) organized the dispersed dairy farmers into Dairy Cooperative Societies (DCS). Fifteen DCS were selected for the study. The facilities obtained by these DCS were elicited through a structured questionnaire. Study indicated that 46.6% DCS received medium level input followed by 26.6 % DCS who got both high and low level of input facilities through AACP. Study also revealed that 100% DCS have connection with dairy development department followed by 80% DCS having free vaccination facility, only 13.3% have the facility of A.I. Study revealed that 86.6 % DCS got training facility followed by 73.3% who got fodder seed and milking instrument. Again 66.7% DCS got constant advice from various department followed by 46.7% who got concentrated feed. Moreover 3.3% DCS got the facility of cycle, 6.7% got furniture facility followed by 20% DCS who got computer facility. The study also revealed that AACP gave monetary, milk selling and transportation facility to 53.3%, 33.3% and 6.5% DCS respectively.